Relevansi dan Tantangan Nilai Nilai Pancasila di Era Digital - Raditya Arya Pamungkas; Devina Vita Tanudjaja; Gandris Rahmadillah; Diajeng Ayu Kartini; Nabil Edika M.A; Seto Cahyono (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
Pancasila is a guideline in life that guides the formation of character to become better and considers the norms and values contained within an individual. This study aims to analyze how the implementation of Pancasila values can be realized in the digital era. The method used is a literature study (library research) by reviewing various journals, books, and scientific sources related to the relevance and challenges of Pancasila in the digital era. The results of the study show that most people have implemented Pancasila values through attitudes of mutual respect, mutual care, upholding tolerance, being responsible in all actions, and actively participating in creating a safe and harmonious social media environment in the digital era. This study concludes that strengthening the implementation of Pancasila in the digital era can contribute to the development of ethical, integrity-driven, and nationally aware character. nationality. Therefore, it is necessary to make efforts for self-awareness to continue upholding the values of Pancasila by shaping oneself according to the principles contained in Pancasila.